COMPUTERIZED MEDICINES SUPPLY MANAGEMENT IN DJAKARTA PHARMACIES - Andre Wijaya; Djoko Harmanto, MS (Jurnal Sistem Informasi, 1989)
This study aims to discuss the computerization of drug supply management, withemphasis on the design of drugs code. In this research, case studies taken atpharmacies Djakarta.To implement the above objectives do some research on the old system of documentflow, kenutuhan user, operational costs, time data processing.From the results of this research note that the calculation of inventories of time longenough and often times the information produced errors that do not support theprocess of inventory monitoring and decision making.To overcome the above designed an inventory system with the help of computers toprocess data and present information more accurate and timely manner to support theleadership in decision making.With the implementation of new systems and management of inventory datacalculation becomes faster and more accurate, thus helping the process of achievingorganizational goals.